A cryptic pigment biosynthetic pathway uncovered by heterologous expression is essential for conidial development in Pestalotiopsis fici - Zhang, Peng; Wang, Xiuna; Fan, Aili; Zheng, Yanjing; Liu, Xingzhong; Wang, Shihua; Zou, Huixi; Oakley, Berl R.; Keller, Nancy P.; Yin, Wen‐Bing (Molecular microbiology, 2017)
Summary Spore pigmentation is very common in the fungal kingdom. The best studied pigment in fungi is melanin which coats the surface of single cell spores. What and how pigments function in a fungal species with multiple cell conidia is poorly understood. Here, we identified and deleted a polyketide synthase (PKS) gene PfmaE and showed that it is essential for multicellular conidial pigmentation and development in a plant endophytic fungus, Pestalotiopsis fici. To further characterize the melanin pathway, we utilized an advanced Aspergillus nidulans heterologous system for the expression of the PKS PfmaE and the Pfma gene cluster. By structural elucidation of the pathway metabolite scytalone in A. nidulans, we provided chemical evidence that the Pfma cluster synthesizes DHN melanin. Combining genetic deletion and combinatorial gene expression of Pfma cluster genes, we determined that the putative reductase PfmaG and the PKS are sufficient for the synthesis of scytalone. Feeding scytalone back to the P. fici ΔPfmaE mutant restored pigmentation and multicellular adherence of the conidia. These results cement a growing understanding that pigments are essential not simply for protection of spores from biotic and abiotic stresses but also for spore structural development. Fungal pigments play important roles in UV protection and asexual development but it is a challenge to identify the especially in a plant endophytic fungus, Pestalotiopsis fici. By heterologous expression of a cryptic pigment biosynthetic gene cluster in an advanced host Aspergillus nidulans, the pathway metabolite scytalone from DHN melanin was characterized and provided the chemical evidence that the pigment is essential for spore structural development.